2017
DOI: 10.1001/jamaoncol.2016.3916
|View full text |Cite
|
Sign up to set email alerts
|

Association of Distinct Mutational Signatures With Correlates of Increased Immune Activity in Pancreatic Ductal Adenocarcinoma

Abstract: Signature-based subtyping may guide personalized therapy of PDAC in the context of biomarker-driven prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
214
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(224 citation statements)
references
References 59 publications
8
214
0
2
Order By: Relevance
“…The 4 most frequently altered genes in PDAC, i.e., KRAS (90%), TP53 (60-70%), CDKN2A (40-50%), and SMAD4 (30-40%), have long been known, and whole exome or genome analysis did not reveal new key driver genes with a frequency above 20%, confirming the important mutational landscape heterogeneity of PDAC [17][18][19][20][21]. None of these frequently mutated genes individually defines a clear subtype, although some, like CDKN2A, SMAD4, or MYC, have been shown to have a prognostic impact [22][23][24].…”
Section: Genomic Pdac Subtypesmentioning
confidence: 83%
See 1 more Smart Citation
“…The 4 most frequently altered genes in PDAC, i.e., KRAS (90%), TP53 (60-70%), CDKN2A (40-50%), and SMAD4 (30-40%), have long been known, and whole exome or genome analysis did not reveal new key driver genes with a frequency above 20%, confirming the important mutational landscape heterogeneity of PDAC [17][18][19][20][21]. None of these frequently mutated genes individually defines a clear subtype, although some, like CDKN2A, SMAD4, or MYC, have been shown to have a prognostic impact [22][23][24].…”
Section: Genomic Pdac Subtypesmentioning
confidence: 83%
“…Otherwise, these high-throughput analyses have defined 4 subtypes at the genome level: (i) a stable subtype (20%) with less than 50 structural variations, (ii) a locally rearranged subtype (30%) with significant focal events located on 1 or 2 chromosomes, (iii) a scattered subtype (36%) with widely distributed nonrandom chromosomal damage (<200), and (iv) an unstable subtype with extended (>200) structural variations [19]. Based on published mutational signatures, Connor et al [21] identified 4 main PDAC subtypes that partially overlap with those described above: (i) an age-related subtype (70%), (ii) a double stand break repair group (11%) that partially overlaps with the unstable subtype, (iii) a mismatch repair group (2%), and (iv) a group of unknown etiology. While these subtypes cannot be easily defined in routine practice, they may have an important theranostic value.…”
Section: Genomic Pdac Subtypesmentioning
confidence: 99%
“…platinum-based chemotherapy, or to radiation therapy [84,85]. Moreover, this subtype of PDAC exhibits synthetic lethality with poly(ADP-ribose) polymerase (PARP) inhibitors and might be prone to sensitivity against immune checkpoint inhibitor therapy [86,87,88,89]. Since this is probably one of the most promising concepts for the development of novel therapeutic strategies against PDAC currently being followed, this topic is covered in a separate article of this minireview series.…”
Section: Novel Therapeutic Targetsmentioning
confidence: 99%
“…First, Connor et al, while noting the potential role of immune checkpoint inhibition in specific PDA subtypes, concluded that their classification featured no clinical implications [13]. On the other hand, Bailey et al identified and validated four major pancreatic cancer subclasses, which were associated with distinct histopathologic and clinical characteristics.…”
Section: Genome Sequencing Technologies and Potential Biomarkersmentioning
confidence: 99%